An Infrared Metamaterial Broadband Absorber Based on a Simple Titanium Disk with High Absorption and a Tunable Spectral Absorption Band. Issue 9 (16th August 2020) - Tang, Yinhui; Meng, Dejia; Liang, Zhongzhu; Qin, Zheng; Shi, Xiaoyan; Zhang, Yuhao; Xiong, Ying; Fan, Yandong; Yang, Fuming; Zhang, Lichao; Lv, Jingguang; Qin, Yuxin; et al.
Abstract: A metamaterial absorber is proposed that functions in the medium‐ (3–5 µm) and long‐wavelength (8–12 µm) infrared (medium‐wavelength infrared, MWIR, and long‐wavelength infrared, LWIR, respectively) regions. The proposed design, which consists of periodic cells, can be tuned to achieve single‐band or dual‐band light absorption by changing the periodicity of the structure. Each cell forming the metamaterial absorber consists of a bottom metal plate (Al), a top metal disk (Ti), and an intermediate dielectric medium (Si or ZnS) in which a metal disk (Ti) is embedded. For a period of 0.85 µm, the absorber achieves broadband absorption in the LWIR region, with an average absorption of 92.1%. Further, the absorber shows acceptable tolerance to irradiation at oblique incidence. For a period of 2 µm, a peak absorption of 99.05% is achieved in the MWIR region, thereby providing dual‐band absorption. Tuning the periodicity of the structure enhances the localized surface plasmon resonance, with the absorption mechanism explained by establishing an equivalent parallel LC circuit. The absorption properties demonstrated by the proposed metamaterial absorber are promising for thermal imaging and infrared spectroscopy. Abstract : A metamaterial absorber in the medium (3–5 µm) and long (8–12 µm) wavelength infrared, based on localized surface plasmon resonance and propagating surface plasmon resonance, is proposed. The relationship between absorption and structural parameters is explained by establishing an equivalent parallel LC circuit. The absorber can realize tunable absorption, and the influence of the incident angle on the absorption performance is tolerable.